STATISTICAL CHARACTERISTICS OF THE COMPONENTS OF COAGULATION HEMOSTASIS AND BLOOD OXYGENATION OF RATS WITH EXPERIMENTAL OPIOID INFLUENCE ON THE EARLY STAGES OF CORRECTION. - Paltov Ye. V.; Masna Z. Z.; Chelpanova I. V.; Fik V. B.; Rudnytska Kh. I.; Yuzuch O. V (Вісник проблем біології і медицини, 2022)
. A large number of external toxic factors contribute to the occurrence of a violation in hematological and biochemical status of the body. It is known that free radical oxidation plays an important role in maintaining the transport of electrons in the respiratory chain, inducing the formation of pores in the mitochondrial membrane, which regulate the coupling of respiration with oxidative phosphorylation and is the basis of oxidative processes in mitochondria. Oxidative processes involving activated oxygen metabolites are an integral part of the existence of higher forms of living organisms. It has been established that under extreme influences in the body, redox processes are activated, which lead to the formation of lipo – and hydroperoxides, the further decomposition of which contributes to the formation of endogenous oxygen, necessary for life. Superoxide is one of the main pro-oxidants in the cell, so superoxide dismutase plays a key role in the body’s antioxidant defense. The function of catalase consists in the destruction of toxic hydrogen peroxide, which is formed in the process of various oxidative reactions in the body. These processes directly affect the indicators of coagulation hemostasis and the degree of blood oxygenation, triggering a cascade of biochemical and hematological changes that affect the development of pathomorphological changes in the links of the hemomicrocirculatory channel and contribute to the violation of normal hemodynamic indicators. The purpose of the study is to establish indicators of coagulation hemostasis and the degree of blood oxygenation in the early stages of opioid exposure during its withdrawal with subsequent correction. When conducting our research, we used 78 white sexually mature outbred male rats, weighing 160-200 grams, which were injected intramuscularly with the drug «Nalbuphine» for 42 days. The number of platelets, prothrombin time, prothrombin index, recalcification time, total fibrinogen, hemoglobin and hematocrit value were determined in the blood of experimental animals at different times of opioid exposure. The obtained data were tested for normality using the Shapiro-Wilk test. The non-parametric Kruskel-Wallis H test for three or more independent groups was used to determine the significance of the difference between groups, followed by post hoc analysis using Dunn’s test. R v 4.0.3 and RStudio v 1.2.5042 software were used to perform statistical calculations. During the sixth week, the changes in the correction subgroup «cancellation + pentoxifylline» – the values of the indicators were as close as possible to the values of the corresponding indicators of the control group.